2012
DOI: 10.1111/tpj.12036
|View full text |Cite
|
Sign up to set email alerts
|

BAT1, a putative acyltransferase, modulates brassinosteroid levels in Arabidopsis

Abstract: SUMMARYBrassinosteroids (BRs) are essential for various aspects of plant development. Cellular BR homeostasis is critical for proper growth and development of plants; however, its regulatory mechanism remains largely unknown. BAT1 (BR-related acyltransferase 1), a gene encoding a putative acyltransferase, was found to be involved in vascular bundle development in a full-length cDNA over-expressor (FOX) screen. Over-expression of BAT1 resulted in typical BR-deficient phenotypes, which were rescued by exogenousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 73 publications
5
35
0
Order By: Relevance
“…A role of BR catabolism in patterning BZR1 is confirmed by the increased nuclear BZR1 levels in the QC and stem cell regions of the bas1;sob7 double mutant, which is defective in two BR-inactivating enzymes expressed in the root tip region. A recent study showed that another BR-inactivating enzyme, BAT1, is also expressed in the root tip region [45]. While BR synthesis and catabolism are required for normal BZR1 patterning, differential BR sensitivity may also contribute to the BZR1 patterning, as BR treatment and the bzr1-1D mutation reduced, but did not completely abolish, the BZR1 gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role of BR catabolism in patterning BZR1 is confirmed by the increased nuclear BZR1 levels in the QC and stem cell regions of the bas1;sob7 double mutant, which is defective in two BR-inactivating enzymes expressed in the root tip region. A recent study showed that another BR-inactivating enzyme, BAT1, is also expressed in the root tip region [45]. While BR synthesis and catabolism are required for normal BZR1 patterning, differential BR sensitivity may also contribute to the BZR1 patterning, as BR treatment and the bzr1-1D mutation reduced, but did not completely abolish, the BZR1 gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, auxin treatment increased cytoplasmic localization of BZR1 in the elongation zone, and inhibiting auxin biosynthesis increased nuclear BZR1 in the root tip region, where the endogenous auxin level is at a maximum. Auxin increases the expression levels of several BR catabolic enzymes, including BAS1, SOB7, BAT1, and BEN1 (Table S4; [45]). These observations suggest that the auxin gradient contributes to the complementary pattern of nuclear BZR1 in root tip, at least in part by promoting local BR catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Pending biochemical confirmation, BAHD acyltransferases, such as BIA1 and PIZ, might act redundantly in BR inactivation. Additionally, BAT1 (putative BR-related acyltransferase), a putative acyltransferase involved in BR inactivation, was identified by the FOX hunting technique (Choi et al, 2013). The BAT1 overexpression line showed a substantial decrease in the level of 6-deoxoTY, TY, and 6-deoxoCS, and exhibited a growth-retarded phenotype, as seen in the BR dwarf mutants.…”
Section: Br Inactivation By Modificationmentioning
confidence: 99%
“…The subclade in blue was used for the tree-reconciliation analysis ( A ). Characterized BAHD acyltransferases from Arabidopsis are numbered, clockwise, and marked on the tree with orange circles; (1) At5g48930, HCT/HYDROXYCINNAMOYL-COA SHIKIMATE/QUINATE HYDROXYCINNAMOYL TRANSFERASE [62]; (2) At2g19070, SHT/SPERMIDINE HYDROXYCINNAMOYLTRANSFERASE [63]; (3) At5g41040, ASFT/ALIPHATIC SUBERIN FERULOYL TRANSFERASE [64]; (4) At3g48720, DCF/DEFICIENT IN CUTIN FERULATE [32]; (5) At5g63560, FACT/FATTY ALCOHOL:CAFFEOYL-COA CAFFEOYL TRANSFERASE [65]; (6) At1g65450, GLC/GLAUCE [66]; (7) At4g31910, DRL/DWARF AND ROUND LEAF 1 [67]/BAT1/BR-RELATED-ACYLTRANSFERASE [68]/PIZ/PIZZA [69]; (8) At3g29670, PMAT2/PHENOLIC GLUCOSIDE MALONYLTRANSFERASE 2 [70]; (9) At5g67160, EPS2/ENHANCED PSEUDOMONAS SUSCEPTIBILITY 1 [71]. The full gene tree (with complete gene identifiers and scale) is provided in the supplemental information.…”
Section: Figurementioning
confidence: 99%